2007
DOI: 10.1016/j.ejpain.2006.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Medical undergraduate students' beliefs and attitudes toward pain – How do they mature?

Abstract: At the University of Helsinki, pain-related topics are taught throughout medical studies but without a formal pain curriculum. The purpose of this study was to assess medical students' attitudes towards pain. A questionnaire using a 6-point Likert scale was constructed to measure pain-related attitudes and beliefs described in previous studies. After a pilot study, the questionnaire was developed to assess attitudes towards elderly patients' pain, prescription of opioids, assessment of pain and anxiety concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 19 publications
0
39
0
2
Order By: Relevance
“…So, the specific and formal teaching about pain in general during medical qualification is minimal and mainly addresses surgical questions, while during specialization in Pediatrics and Neonatology, teaching is during daily practice, depending on the concepts and prejudices of physicians teaching residents. The shortage of teaching about pain in different age groups in medical courses has been reported by different authors [20][21][22][23] . In the University of Helsinki, where there was no formal pain course at the time of the study, 430 medical students were interviewed 21 and it was found that attitudes about pain evaluation and treatment have matured along the graduation years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So, the specific and formal teaching about pain in general during medical qualification is minimal and mainly addresses surgical questions, while during specialization in Pediatrics and Neonatology, teaching is during daily practice, depending on the concepts and prejudices of physicians teaching residents. The shortage of teaching about pain in different age groups in medical courses has been reported by different authors [20][21][22][23] . In the University of Helsinki, where there was no formal pain course at the time of the study, 430 medical students were interviewed 21 and it was found that attitudes about pain evaluation and treatment have matured along the graduation years.…”
Section: Discussionmentioning
confidence: 99%
“…The shortage of teaching about pain in different age groups in medical courses has been reported by different authors [20][21][22][23] . In the University of Helsinki, where there was no formal pain course at the time of the study, 430 medical students were interviewed 21 and it was found that attitudes about pain evaluation and treatment have matured along the graduation years. Other authors indicate that a multidisciplinary curriculum on pain improves practical actions of medical students and residents in terms of pain evaluation and treatment in different age groups [20][21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these surrogates is the attitude toward pain [2,3,6,16]. Measurement tools have been the actual perception of main symptoms, active inquiries on the duration, quality and intensity of pain, pain quantification (for example through visual analogue scale) and the use of analgesic therapy [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the studies done by Turner and Weiner,7 Niemi-Murola, Po¨yhia¨ and Kalso, 8 Po¨yhia¨ and Kalso, 9 Watt-Watson and co-workers, 10 Sloan and co-workers, 11 and Po¨yhia¨and co-workers, 5 in the medical schools they surveyed in the U.S. and Finland, teaching of pain related topics is fragmented, important topics are poorly covered and specifi c curricula for pain are uncommon.…”
Section: Introductionmentioning
confidence: 99%